2014
DOI: 10.1007/s40266-014-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Medication and Associated Factors in an Elderly Population: A Systematic Review

Abstract: Self-medication is frequent among the elderly, with different prevalence values found in the selected studies, probably because of heterogeneity in definitions and samples. Future studies are necessary, utilizing a standard self-medication criterion to facilitate comparison and elucidate the factors associated with this behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 39 publications
5
91
1
6
Order By: Relevance
“…9 In a study in Iran, the prevalence of self-medication was 83%. 11 Lower prevalence is reported in elderly from Brazil with 35.7% of the elderly reported self-medicating, 15 while in the Australian study 97% of the elderly reported using self-medication. 16 The high prevalence of self-medication in older adults could be due to several reasons.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…9 In a study in Iran, the prevalence of self-medication was 83%. 11 Lower prevalence is reported in elderly from Brazil with 35.7% of the elderly reported self-medicating, 15 while in the Australian study 97% of the elderly reported using self-medication. 16 The high prevalence of self-medication in older adults could be due to several reasons.…”
Section: Discussionmentioning
confidence: 92%
“…[8][9][10] A review of 28 articles on self-medication by elderly found the prevalence of selfmedication between 4 and 87% with majority reporting between 20% and 60%. 11 To our knowledge, only a few studies have been reported from India. 12 Hence, this cross-sectional study was conducted to evaluate the prevalence and pattern of self-medication in elderly at a tertiary care hospital in Ahmedabad city of Gujarat state in India.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with the reported symptoms (fever and general body or muscular pains) that are associated with these categories of medicines. Use of analgesics and/or antipyretics as the most frequent categories of drugs used for SM have been reported from studies that were conducted in Nigeria and Ethiopia [21,26,27] . In poor resource countries like Tanzania, it is expected patients to use antipyretics and analgesics for common illnesses like fever, headache and body pains; when used correctly, they are very effective.…”
Section: Short Communicationsmentioning
confidence: 99%
“…Resistance to antibiotics would allow the infections that were thought to be treatable 15 years ago to emerge as main threats to public health again. 6 An important factor in self-medication, which has been widely emphasized in different studies, is selling drugs without the doctor's prescription. 7 This will result in the factors including increased drug consumption per capita, resistance to drugs, lack of optimum treatment, poisoning, unexpected consequences, etc.…”
Section: Introductionmentioning
confidence: 99%